Importance-Performance Analysis of SINERGI UPI Website User Satisfaction - Linda Setiawati; Angga Hadiapurwa; Budi Santoso; Hafsah Nugraha; Ridha Pratama Rusli (Jurnal Edutech Undiksha, 2024)
SINERGI UPI is a dynamic archive management system at Universitas Pendidikan Indonesia (UPI). The use of SINERGI within UPI needs to be pursued for optimal management of dynamic archives. One thing that needs to be considered is the user satisfaction component to create a good impression for the academic community as SINERGI users. This research was conducted to analyze SINERGI from the aspect of user satisfaction. The research uses a quantitative approach with survey methods. The survey was conducted among study program staff within the Faculty of Educational Sciences UPI who actively use SINERGI, namely thirteen people. The data analysis technique uses Importance-Performance Analysis (IPA). The research results illustrate that all indicators fall into quadrant II: Keep up the good work. This shows that the SINERGI user satisfaction of the FIP UPI academic community is satisfied with the SINERGI facilities, and it is hoped that it will be even better in the future. However, there are hopes and suggestions for improvements for the future development of the SINERGI website, namely in the menu bar and notifications. Some staff expect an additional menu, namely notifications sent via email or WhatsApp. This is to make it easier when there is an incoming letter notification so that the staff can respond immediately. There is also another proposal in the form of a follow-up workshop related to using SINERGI at a higher level.